Data-driven method for online power system emergency control - Zhou, Zheng (Nanyang Technological University, 2022)
In recent decades, electricity has been involved in almost all aspects of human society. And as the transporter of electricity, power system is being more and more important, or power system can be called the guarantee of electricity. Power system is usually stable, but sometimes it will also have some faults. Especially when nowadays the penetration of renewable energy such as wind energy and photovoltaic energy is increasing, they may make it more challenging to maintain the system’s stability. The increased penetration of these new energies affects the transient and stable stability of power system a lot for their unpredictability. So, there should be some solutions for emergency control against instability. This paper proposes a data-driven method to decide the load shedding range as a power system emergency control method.